Techniques of Marketing Library Services and Facilities: A Case Study of Ashanti Regional Library (Journal of Science and Technology, 2016)
The paper discusses a number of techniques that are used in marketing library services and facilities. These include the use of the mass media, newsletters, leaflets, Flyers, brochures, signposts, shelf labels, catalogues (catalogue cards and Online Public Access Catalogue-OPAQ and current awareness services. The application of these marketing tools at the Ashanti Regional Library to Kumasi and the shortcomings observed during a survey at the library have also been discussed. A number of suggestions towards improving the marketing of the library so as to increase its patronage have been offered. It is hoped that maximum use will be made of the library} services and facilities if the suggestions are favourably considered.